2011
DOI: 10.1186/1471-2431-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Characterization of a Cohort of Pediatric Wilson Disease Patients

Abstract: BackgroundIn Egypt, Wilson disease seems to be under diagnosed and clinical data on large cohorts are limited. The aim of this study is to highlight the clinical, laboratory and genetic characteristics of this disease in our pediatric population as well as to report our experience with both treatment options and outcome.MethodsThe study included 77 patients from 50 unrelated families (62 were followed up for a mean period of 58.9 ± 6.4 months and 27 were asymptomatic siblings). Data were collected retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…These features attest to the importance of divergence or variability in the clinical profile in different population groups implying the role of ethnic and geographic factors. The higher proportion of males with WD and ALF concurs with those reported from the King's College group and other studies . The greater frequency of girls appears to be restricted to a post pubertal age group and cannot be extrapolated to prepubertal children.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These features attest to the importance of divergence or variability in the clinical profile in different population groups implying the role of ethnic and geographic factors. The higher proportion of males with WD and ALF concurs with those reported from the King's College group and other studies . The greater frequency of girls appears to be restricted to a post pubertal age group and cannot be extrapolated to prepubertal children.…”
Section: Discussionsupporting
confidence: 87%
“…Wilson disease, is an autosomal recessive disease involving the ATP 7B gene whose reduced or nonfunction results in accumulation of hepatic copper culminating in liver injury . A rare disease with a prevalence of approximately one in 30 000 US population, it affects the young from all racial backgrounds and is more common in countries where consanguineous marriages are prevalent . Primarily a disease of childhood and adolescence, it has been reported in the elderly .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…effect of the same mutation in different Han Chinese pedigrees with WD, which may account for the high allele frequencies of mutations p.Arg778Leu, p.Pro992Leu, and p. Ala1295Val in Asia, rather than mutation hotspots [22]. Previous studies on Japanese and Egyptian children with WD showed that genotypes for truncation of ATP7B were established to be associated with an early onset and fulminant or acute liver failure [31][32][33][34]. Consistently, the onset age of our patients (combined with our previous data) with protein-truncating mutations ranges from 2 to 20 years old (mean onset age: 12.3 ± 5.9 years old), while that of our patients with missense mutations ranges from 6 to 41 years old (mean onset age: 19.9 ± 10.9 years old) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite identification of the sole mutated gene, ATP7B, and increased understanding of Wilson disease ATPase function in hepatocytes, associations between genetic mutation and clinical phenotype remain incompletely understood. [1][2][3] Liver dysfunction in WD ranges from mild aminotransferase elevation to fulminant hepatic failure. Extrahepatic findings, with or without apparent liver injury, including neuropsychiatric, endocrine, hematologic, and renal abnormalities, result in a complex clinical spectrum that may lead to delayed or inaccurate diagnoses.…”
Section: Discussionmentioning
confidence: 99%